Design and analysis of a flexure-based modular precision positioning stage with two different materials. Issue 3 (26th February 2018) - Ding, Bingxiao; Li, Yangmin; Xiao, Xiao; Wu, Zhigang
Abstract : Purpose: Generally, the motion range of the micro scale operation is within several hundreds of microns, and the conventional joints cannot satisfy the requirements due to manufacturing and assembling errors, hysteresis and backlash in the joints. The paper aims to discuss these issues. Design/methodology/approach: The following issues should be considered: a micromanipulation stage should be designed using a small-dimensional scale driven by the small size of piezoelectric actuator and the components can be replaced due to fatigue failure caused by repeated cyclic loading. This paper proposes a modular design of a flexure-based 2-DOF precision stage made using aluminum (T6-7075) material and Acrylonitrile Butadiene Styrene plastic material. The piezoelectric actuator is adopted to drive the stage for the fast response and large output force. To compensate the stroke of piezoelectric actuator, a bridge-type amplifier is designed with optimized structure. Findings: The simulation results validate the advantages of modular positioning stage fabricated by two different materials. Research limitations/implications: The stage can be used in micro scale precision's applications. If it will be used in nanoscale precision, then some sensors in nanoscale of measurement should be used. Practical implications: The designed stage can be used in biomedical engineering, such as cell injection testing, etc. Social implications: The designed stage will be used in micro/nanoengineering field, such as micro/nanomanufacturing or assembly, manipulation of cell, etc., which will push forward high technology to a higher level. Originality/value: Two kinds of materials have been selected to make the positioning stage, which are seldomly found in literature on compliant mechanism field. A modular design concept is proposed for the positioning stage design.